Social skills in late childhood and their influence on coping with stress - Hendrie Kupczyszyn, Karina Noelia (2021)
The present study aims to describe social skills in the late childhood and to analyze the ways in which they influence the ability to cope with stress. Social skills are defined as specific and necessary social dexterities to adequately perform an interpersonal task. They allow the expression of feelings, desires, attitudes, opinions and rights in an appropriate way. Therefore, they are of great value when it comes to strengthening relationships, adjusting to environmental demands and selecting adaptive strategies to cope with stress. An empirical, quantitative, ex post facto study was conducted with a sample of 223 children of both sexes, between 9 and 12 years old (M = 10.61, SD = 1.10), from the provinces of Chaco and Misiones, Argentina. The measuring instruments used in this research were the Argentine Coping Questionnaire for Children and the Appropriate Social Skills Subscale of Matson, validated in Argentina. The results showed the presence of a moderately high level of social skills in children, without differences due to gender or age. Through multivariate analysis of variance (MANOVA) analysis, a significant influence of social skills on coping with stress was observed. Children who obtained high scores in measurements of social skills showed also high scores in logical analysis, cognitive restructuring, proactive problem-solving, a propensity to seek advice and support, and lower values of emotional release.